Perlindungan Hukum Terhadap Tidak Terpenuhinya Hak Anak Akibat Perceraian dari Perkawinan Campuran (Studi Putusan Pengadilan Nomor: 502/PDT.G/2018/PN.JKT.PST) - Arfan, Vina Raudhathul; Aminah, Aminah (UNES Law Review, 2024)
Mixed marriages are marriages between men and women who have different citizenship and rule of law and one of them is an Indonesian citizen as regulated in Article 57 of Law Number 16 of 2019 Amendments to Law Number 1 of 1974 about Marriage. Children's rights are part of human rights. However, it becomes a polemic if it turns out that the court decision cannot provide legal protection for children's rights. Focus of this research is 1. How is legal protection the children's rights due divorce from a mixed marriage? 2. How is the solutions of legal protection of children's rights due to divorce from mixed marriages?. The research method used is descriptive analytical with a normative juridical approach. The results of this research is that it can be concluded that the obligations and responsibilities of parents to children are not interrupted even though the parents already divorce. With the divorce from mixed marriages, the children’s rights must be protected according to the legal regulations in force in the country of origin from both parents. To protect children’s rights in divorce from mixed marriages, the solution is that the nation make a new laws and regulations regarding legal protection of children’s rights from mixed marriages.